Removal of Methylene blue, Escherichia coli and Pseudomonus aeruginosa by Adsorption Process of Activated Carbon Produced from Moringa oleifera Bark - Md. Shahin Azad; Syaza Azhari; Mohd Sukri Hassan (USIM Press, 2024)
MJoSHT2020, Volume 7, Special Issue, eISSN: 2601-0003